Effect of the complex of C60 fullerene with doxorubicin on tumor cells in vitro and in vivo - Prylutska, S.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
A technological scheme for preparing a stable aqueous solution of C60 fullerene with an antibiotic doxorubicin (Dox) of the anthracycline row is proposed. The toxic effect of the C60+Dox complex on cells of Ehrlich ascites carcinoma, leukemia L1210, and Lewis lung carcinoma is demonstrated. Its antitumor effect on Lewis lung carcinoma in vivo was also shown. Thus, a high efficiency of the C60+Dox complex in the anticancer therapy is postulated.